Sintesis Surfaktan Metil Ester Sulfonat (MES) Dari Palm Oil Metyhl Ester (POME) Dan Natrium Bisulfit (NaHSO3) Dengan Variasi Suhu Sulfonasi Dan Rasio Mol Pome : NaHSO3 - Yuliatmi Yuliatmi; Syaiful Bahri; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Methyl Ester Sulfonate (MES) is an anionic surfactant which is currently being developed. These surfactants can be produced from palm oil methyl ester. MES produced from sulfonation reaction with addition of sulfonation agents. MES can be synthesized from Palm Oil Methyl Ester (POME) and Sodium Bisulfite (NaHSO3) as the sulfonation agent with Calcium Oxide as the catalyst. The aims of this research are to determine the characteristic of the product, and to determine the effects of temperature and mole ratio of the product produced. Sulfonation process was carry out at the temperature of 80, 100, 120°C, the mole ratio of 1:1, 1:1,5, 1:2, the stirring speed of 450 rpm, and the time of 6 hours. Then purification of the MES surfactant and product analysis is carried out. The best characteristic of the MES is at temperature 100°C and mole ratio 1:2 with the density of 0,860 gr/ml, the viscosity of 1,966 cP, the pH of 3,53, the surface tension of 37,45 dyne/cm, the interfacial tension of 26,3 dyne/cm, the emulsion stability of 89%, and the yield of 83,25%.The surface tension is accordance to the commercial MES.Keyword : MES, POME, Sulfonation, Surfactant, Surface Tension.